The effect of gradual flour addition during kneading on wholewheat dough properties and bread quality. (July 2021) - Parenti, Ottavia; Guerrini, Lorenzo; Carini, Eleonora; Zanoni, Bruno
Abstract: The increasing interest in unrefined flour-based products demands innovative strategies to improve dough properties and bread quality. This study investigated the effect of an empirical practice used by bakers – gradual flour addition during kneading – on wholewheat flour dough properties and bread quality. After optimizing the kneading operating conditions to perform gradual flour addition during kneading, a full factorial design tested gradual flour addition in the optimized dough samples as a function of total water content. Although gradual flour addition did not affect bread quality, the dough extensibility – L and swelling index – G improved significantly independently of the total water content. Significant interaction was observed between gradual flour addition and dough water amount; a reduction of dough tenacity – P and tenacity-to-extensibility ratio – P/L at Farinograph water absorption, and an increase of dough tenacity – P and flour strength – W at the highest water level were observed. Furthermore, the 1 H NMR results revealed different water redistribution and dynamics which could be interpreted as molecular phenomena associated with the macroscopic parameters. Gradually adding flour during kneading improved the rheology and workability of unrefined dough. Highlights: The kneading conditions were optimized to perform the gradual flour addition. The interaction gradual flour addition ( F ) – water ( W a ) affected 1 HNMR parameters. F increased dough extensibility and swelling index independently of water content. The interaction F * W a showed additional rheological improvements. Gradual flour addition improved the rheology and workability of unrefined dough.